Design and Optimization of a Modified CoLar System for Biogas Agroindustry Development: Case Study at PT Juang Jaya Abdi Alam, South Lampung Regency - Z. A. Maktub; S. Hidayati; T. P. Utomo; E. Suroso (JOBC, 2025)
One of the efforts made by the government to achieve national beef self-sufficiency is increasing cattle farming. However, while providing benefits, this increase also has negative impacts, particularly in the form of improperly managed cow manure waste that can cause environmental pollution. This study aims to design and optimize a biogas reactor system based on the Modified Covered Lagoon Anaerobic Reactor (CoLAR) for the development of a biogas agro-industry, as a solution for processing cow dung waste through anaerobic biological processes on an industrial scale. The case study was conducted at PT Juang Jaya Abdi Alam, South Lampung Regency, which produces approximately 198,000 kg/day of organic waste from 8,500 to 9,500 cows, most of which has not been optimally utilized. The methods used in this research include observation, expert interviews, surveys, and literature review. The most appropriate reactor type was selected using the Exponential Comparison Method (MPE). This multi-criteria decision-making approach applies weighted scores to technical, environmental, and financial criteria. Three reactor types were evaluated, namely Complete Mix, Plug Flow, and Modified CoLAR. Based on expert scoring, Modified CoLAR was identified as the most suitable option. The designed system consists of a dilution unit, mixing unit, solid-liquid separator, and an anaerobic reactor with an internal stirring system and an HDPE geomembrane cover. The results showed that the Modified CoLAR was the most suitable option, with a total reactor volume of 11,935 m³, biogas production of 1,663.2 m³/day, methane gas volume of 1,092.72 m³/day, and an electricity generation potential of 5,135.784 kWh/day.